Feasible media mix for dissemination of forest conservation support information (FCSI) in South Western Nigeria (2006)
This paper reports tile potentials of media mix in use for agricultural information dissemination as applied to dissemination of information on forest conservation and sustainable land use practices in three southwestern states of Nigeria. It covered enclaves in Shasha and Oluwa forest reserves in Oshun and Ondo states respective, as well as settlements surrounding Old Oyo National Park in Oyo State. The media considered were traditional and electronic/print Primary data were sourced through administration of open-ended and structured questionnaires and use of focus group discussions (FGDs) and rapid rural appraisal (RRA) technique of 20% of the settlements in and around the study sites. Data generated were analyzed using descriptive and inferential statistics. Result showed that an average of 69.0% of the inhabitants had at least a functional radio set, while 6.5%, 5.6% and 1.2% had access to pamphlets, newspaper/magazine, and television sets respectively. In the case of traditional media, town criers, was mostly favoured (46%), while 6.0% and 37.1% of the inhabitants favoured the use of folklore, songs and festivals/religious gathering respectively is therefore no common medium accessed by all respondents ( F= 4.02; dfr = 2536; Pr. < 0.02) although, from inhabitants' perspectives, traditional and modern media messages are found to compliment each other (F= 23.6; dfr. = 253; Pr. < 0.01). In addition, the mix most favoured by inhabitants for sourcing information on sustainable land use in the study area was found to be community/religious leaders, and radio (34.9%). So also, the most appropriate media mix for the dissemination of forest conservation/sustainable land use practices in the study area is the Village/religious fora and radio (45.8%). Thus, public change institutions, which were found to be important to one-on-one information dissemination, must be beefed up to meet optimal performance standard. Also, other relevant media should be explored to meet the target audience requirements for accessing FCSI